Kokka-tarinoita - Anonymous (Salt Lake City, UT : Project Gutenberg, 2015)
"Kokka-tarinoita" by Anonymous is a collection of anecdotes written during the early 19th century. The book presents a variety of stories that touch upon the follies and wisdom of human behavior, often blending humor with moral lessons. It is intended for a general audience, likely reflecting the societal norms and issues of its time. The contents of "Kokka-tarinoita" consist of short tales that illustrate various interactions between characters from different walks of life, including peasants, nobles, and common folk. Each story often ends with a humorous twist or a thought-provoking moral, highlighting the absurdities of social norms, misunderstandings, and the quirks of human nature. For example, one tale recounts the futile attempts of a man and his son to satisfy everyone$1 (Bs expectations while traveling with their donkey, ultimately leading to a comically foolish decision. The overarching theme emphasizes the importance of personal judgment over societal pressure, reflecting a timeless aspect of human experience. (This is an automatically generated summary.)s
Release date is 2015-02-04
E-text prepared by Jari Koivisto
Keywords: Fables, Finnish